Organic Cocrystals: Recent Advances and Perspectives for Electronic and Magnetic Applications - Jiang, Mengjia; Zhen, Chun; Li, Shuyu; Zhang, Xiaotao; Hu, Wenping (Frontiers in Chemistry, 2021)
Cocrystal engineering is an advanced supramolecular strategy that has attracted a lot of research interest. Many studies on cocrystals in various application fields have been reported, with a particular focus on the optoelectronics field. However, few articles have combined and summarized the electronic and magnetic properties of cocrystals. In this review, we first introduce the growth methods that serve as the basis for realizing the different properties of cocrystals. Thereafter, we present an overview of cocrystal applications in electronic and magnetic fields. Some functional devices based on cocrystals are also introduced. We hope that this review will provide researchers with a more comprehensive understanding of the latest progress and prospects of cocrystals in electronic and magnetic fields.